1984
DOI: 10.1029/ja089ia11p09771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot electrons on the polar wind

Abstract: A semikinetic model was used to study the effect that hot electron populations have on the polar wind. The model was used to describe the steady state plasma flow along diverging geomagnetic field lines in the collisionless regime at high altitudes. The plasma contained O+ and H+ ions and both hot and cold electron populations. Several hot electron populations were considered, including the polar rain, polar showers, and polar squall. Estimates of hot electron parameters based on characteristic energy and flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 12 publications
(19 reference statements)
5
68
0
Order By: Relevance
“…Even if the effects of the escaping photoelectrons were important, it is still expected that the day-night density asymmetry is in large part controlled by the cleft ion fountain, as demonstrated in the present simulations. Effects of polar rain were not incorporated in the simulations either, since previous studies suggested that their accelerating effects are important at altitudes higher than 3-4 R E (Barakat and Schunk, 1984;Ho et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the effects of the escaping photoelectrons were important, it is still expected that the day-night density asymmetry is in large part controlled by the cleft ion fountain, as demonstrated in the present simulations. Effects of polar rain were not incorporated in the simulations either, since previous studies suggested that their accelerating effects are important at altitudes higher than 3-4 R E (Barakat and Schunk, 1984;Ho et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Classical polar wind models are not able to predict O þ escape. Additional mechanisms that can explain how O þ ions are accelerated out of the ionosphere are: wave-particle heating by broadband emissions (Barghouthi, 1997), field-aligned potential drops set up by field-aligned currents (Mitchell et al, 1990;Ho et al, 1992;Barakat and Schunk, 1984; Barakat et al, 1998), hot and cold (thermal and photo) electron populations interacting with each other (Moore et al, 1999a;Su et al, 1998a,b;Schunk, 2000), centrifugal acceleration owing to convection, and flux tube compression and dilation (Horwitz, 1987;Cladis et al, 2000;Swift, 1990;Horwitz et al, 1994). With increasing height ion inertia, dynamic effects, and convection become increasingly important (Banks and Kokarts, 1973;Swift, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…Wilson et al [1997] argued that this mechanism was the most reasonable, and in kinetic simulations Wilson et al [1997] and Su et al [1998] were able to find zero current solutions without cold electron inflow or heavy ion outflow by inserting double layers with potential drops of tens of eV. One possible formation mechanism for these double layers is a contact discontinuity which forms between the cold ionospheric electron gas and the hot magnetosheath electron gas [Barakat and Schunk, 1984;Barakat et al, 1998b]. The simulations of Barakat et al [1998b] show that these double layers form between 2 and 6 R E in altitude, and their locations are highly dynamic as the field lines convect through different regions.…”
Section: 1002/2013ja019378mentioning
confidence: 99%